Seismic good quality of the Earth crust of the northern part pf the Ukrainian shield - Yu. A. Andrushchenko; V. I. Osadchyi; O. I. Lashchuk; V. V. Grabchenko (Геофизический журнал, 2016)
According to the records of superficial coda-waves from seismic events in the Kriviy Rig area receive value, quality factor (Q), frequency parameter (n) and attenuation factor (δ) of seismic waves in earth's crust of northern part Ukrainian shield have been obtained. To determine the quality factor digital recording of seismic signals from the area of Kriviy Rig produced network of seismic observations of the Main center of the special control (MCSK) over the last 10 years were used. The resulting empirical relationship for the northern part of the Ukrainian shield Qc(f) was used to clarify the formula for calculating the magnitude of the surface on the Lg-wave. Based on these data, the conclusion on the present level of tectonic activity in the study area has been made.